1998
DOI: 10.1046/j.1365-2249.1998.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Mercury-induced autoimmunity in the absence of IL-4

Abstract: In susceptible H‐2s mice, mercuric chloride (HgCl2) induces an autoimmune syndrome characterized by production of anti‐nucleolar antibodies (ANoA) and increased serum levels of IgG1 and IgE antibodies. The increase in serum IgG1 and IgE, which are under IL‐4 control, suggests a role for the Th2 subset in the induction of this syndrome. We have previously shown that administration of IL‐12, a potent Th1‐promoting cytokine, resulted in a dramatic reduction of the HgCl2‐induced anti‐nucleolar antibody titres and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
25
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 34 publications
9
25
0
Order By: Relevance
“…Furthermore, the similar levels of serum total IgE between anti-CTLA-4-treated and control groups also support our previous hypothesis that different regulatory mechanisms control the various aspects of the syndrome (31). Most of the increase in serum IgG1 and IgE Igs during HgCl 2 -induced autoimmunity is polyclonal in nature and not targeted against a specific Ag.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the similar levels of serum total IgE between anti-CTLA-4-treated and control groups also support our previous hypothesis that different regulatory mechanisms control the various aspects of the syndrome (31). Most of the increase in serum IgG1 and IgE Igs during HgCl 2 -induced autoimmunity is polyclonal in nature and not targeted against a specific Ag.…”
Section: Discussionsupporting
confidence: 85%
“…The current finding that lupus-like disease in BXSB mice does not require IL-4 is similar to what has been observed for several other humoral-mediated autoimmune diseases, including mercuryinduced systemic autoimmunity (29,35) and experimental autoimmune myasthenia gravis (EAMG) (41). In the case of EAMG, IL-4 deficiency may in fact facilitate development of disease (42).…”
Section: Discussionsupporting
confidence: 84%
“…In BXSB and MRL-Fas lpr mice, the increases in IL-4 levels and IL-4 producing cells although present are much less than the increases observed in IFN-␥ levels or IFN-␥-producing cells (27,30,34). Knockout of the IL-4 gene had no effect on disease induction in the mercury-induced model of systemic autoimmunity, which was previously considered a prototypic Th2-mediated humoral disease (29,35). Finally, expression of an IL-4 transgene by B cells in (NZW ϫ C57BL/6.Yaa)F 1 mice protected rather than enhanced the development of lupus nephritis, and this protection appeared to be due to deviation of the autoantibody response away from especially pathogenic Th1-mediated IgG subclasses such as IgG3 (36).…”
Section: D4mentioning
confidence: 98%
“…This suggests that this feature of HgCl 2 -induced autoimmunity is BAFF-independent and is consistent with previous findings that mice either transgenic for BAFF or injected with BAFF showed significantly increased levels of serum IgM and IgA, but not IgG (6,34,40). Previous studies of this model have also shown that different features such as ANoA production and polyclonal activation can be individually manipulated (44,45). The present findings confirm that the various manifestations of Hg-induced autoimmunity are separately regulated.…”
Section: Discussionsupporting
confidence: 93%